2013
DOI: 10.1002/jrs.4388
|View full text |Cite
|
Sign up to set email alerts
|

Birth of room‐temperature magnons and Raman line enhancement in ZnO nanostructures containing cobalt oxide

Abstract: Cobalt (Co) addition and thermal annealing induced structural and vibrational properties of ZnO nanostructures were analysed. X‐ray diffraction pattern reveals that the nanostructures are in hexagonal wurtzite type and the formation of Co3O4. The Co ion induced morphology changes have been studied by high‐resolution scanning electron microscope images and energy dispersive spectroscopy measurements confirm the presence of Co ions. CoO‐related magnon excitation bands are emerged at room temperature for the Co‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…This is called the energy–time uncertainty relation; here Δ E is the uncertainty in the phonon mode energy, and ħ is reduced Planck constant …”
Section: Raman Spectral Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is called the energy–time uncertainty relation; here Δ E is the uncertainty in the phonon mode energy, and ħ is reduced Planck constant …”
Section: Raman Spectral Studiesmentioning
confidence: 99%
“…This is called the energy-time uncertainty relation; here ΔE is the uncertainty in the phonon mode energy, and ħ is reduced Planck constant. [35] The phonon lifetime is the combination of anharmonic decay of phonon with the decay time of τ A and translational symmetry loss with a phonon decay time of τ 1 .…”
Section: Phonon Lifetimementioning
confidence: 99%
“…They found that annealed samples exhibit suppression of magnon bands and formation of Co 3 O 4 : ZnO composites. Raman bandwidth and the electron–phonon coupling constants are decreased relative to increases in the annealing temperature . Patsha et al .…”
Section: Introductionmentioning
confidence: 57%
“…Raman bandwidth and the electron-phonon coupling constants are decreased relative to increases in the annealing temperature. [128] Patsha et al probed the crystallographic orientation of a single GaN nanotubes using polarized Raman imaging. Deviation from polarization selection rules for GaN is attributed to the geometrical anisotropy of the NT, and electron microscopic structural data confirms the spectral imaging analyses.…”
Section: Biomoleculesmentioning
confidence: 99%
“…In the present case, all the spectra show an absorbance band at *450 cm -1 which is assigned to the E 1 (TO) mode vibrations of ZnO [39]. The broad bands at around *3400 and *1640 cm -1 could be assigned to the stretching and bending vibrations of H-O-H bond, respectively [40]. The bands observed at *1350-1450 and *1550 cm -1 are assigned to the symmetric and asymmetric stretching vibrations of COO -modes from the carboxyl groups of acetate in the metal precursors [41].…”
Section: Ftir Studiesmentioning
confidence: 87%